Experiences of Faculty Members in Relation to the Academic Promotion Process - Hossein Karimi-Moonaghi; Akram Zhianifard; Hamid Jafarzadeh; Hamid Reza Behnam; Jalil Tavakol-Afshari (Kerman University of Medical Sciences, 2015)
Background & Objective: One of the most important factors in the evaluation of specific performance indices of each university is the professional maintenance and promotion of faculty members This will result in more desirable output results from this system The aim of this study was to explore describe and interpret faculty members experiences of the academic promotion process and its obstacles and problems Methods: A phenomenological approach was used in this research The study population consisted of 22 faculty members of Mashhad University of Medical Sciences Iran who were selected through purposeful sampling Data were collected through semistructured interviews and analyzed using the van Manen method Results: The main theme of passing the academic promotion marsh and 5 subthemes emerged from data analysis The subthemes consisted of problems related to administrative processes problems related to the performance of committees problems related to general competence problems related to the academic promotion guideline and motivational factors Conclusion: Our findings emphasize the problems and barriers of the promotion process Quality assessment homogenization of processes and the use of experts in college committees are some of the factors that affect the promotion process The findings of this study can assist policymakers and administrators of Medical Sciences Universities at different levels in decision making and finding solutions to facilitate the academic promotion process and rectify its problems and obstacles